RESISTING CLOSURE: THE REPRESENTATION OF OPHELIA ON PAINTING AND SCREEN - Vieira, Érika Viviane Costa (Em Tese, 2005)
Based on representations of the character of Ophelia invisual arts and in the readings of traditional literarycriticism of Shakespeare, this paper seeks to question aperverse aesthetics that conjoins women and death.